2020
DOI: 10.1002/pits.22447
|View full text |Cite
|
Sign up to set email alerts
|

Dual factor mental health model: Validation through mixture modeling and cut scores

Abstract: The dual-factor model (DFM) of mental health affords educators an expanded view of student social-emotional and behavioral functioning and may help identify students in need of school-based mental health services who would otherwise go unnoticed with traditional screening methods. With a focus on integrating subjective well-being into

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Instead, we identified a partially symptomatic and content profile, with only moderate mental well-being and moderate ED symptomatology. While symptomatic but content profiles have been identified in previous research using different methods to derive mental health profiles (Keyes, 2005;Renshaw & Cohen, 2014), other LPA dual continua studies have found results similar to the present study (Khumalo et al, 2022;Moore et al, 2019aMoore et al, , 2019bThayer et al, 2021). For example, in a study of African and South African university students, Khumalo et al (2022) used LPA and found a profile of students who had moderate wellbeing and moderate depressive symptoms (i.e., partially symptomatic and content), and no profile where students endorsed high well-being and high depressive symptoms (i.e., symptomatic but content).…”
Section: Discussionsupporting
confidence: 84%
“…Instead, we identified a partially symptomatic and content profile, with only moderate mental well-being and moderate ED symptomatology. While symptomatic but content profiles have been identified in previous research using different methods to derive mental health profiles (Keyes, 2005;Renshaw & Cohen, 2014), other LPA dual continua studies have found results similar to the present study (Khumalo et al, 2022;Moore et al, 2019aMoore et al, , 2019bThayer et al, 2021). For example, in a study of African and South African university students, Khumalo et al (2022) used LPA and found a profile of students who had moderate wellbeing and moderate depressive symptoms (i.e., partially symptomatic and content), and no profile where students endorsed high well-being and high depressive symptoms (i.e., symptomatic but content).…”
Section: Discussionsupporting
confidence: 84%
“…The two-dimensional typology has been confirmed in independent studies of samples of children and adolescents using the cut-score approach (Antaramian et al, 2010;Lyons et al, 2012;Smith et al, 2020;Suldo et al, 2016;Thayer et al, 2021;Xiong et al, 2017) and undergraduates (Antaramian, 2015;Eklund et al, 2011;Magalhães & Calheiros, 2017;Renshaw & Cohen, 2014) using a range of different measures of subjective wellbeing, indicators of psychopathology, and outcomes, albeit with different labels applied to the groups in some of the studies (Eklund et al, 2011;Renshaw & Cohen, 2014). Furthermore, the two-dimensional typology of mental health has also been confirmed in studies of children and adolescents using LPA (Rose et al, 2017;Thayer et al, 2021).…”
Section: Dual Factor Model Of Mental Healthmentioning
confidence: 81%
“…Regarding the mental health groups, 72 manuscripts provided evidence of classifying participants into different groups (e.g., Antaramian et al, 2010;Arslan & Allen, 2022). To classify people, most of them (f = 45; e.g., DiLeo et al, 2022) applied a cut score approach (which means that they used the participants' scores on the well-being and/or psychopathology dimensions to group them into high vs. low), 21 used latent analyses (i.e., profile, class, or transition analyses) (e.g., Clark & Malecki, 2022), one applied discriminant function analyses (i.e., Greenspoon & Saklofske, 2001), three adopted a hierarchical clusters method (e.g., de la Iglesia et al, 2019), one compared the cut score approach with a latent profile analysis (i.e., Thayer et al, 2021), and one was unclear regarding the classification type (i.e. Kim et al, 2022).…”
Section: Mental Health Groupsmentioning
confidence: 99%
“…Regarding the classification methods, most of the reviewed studies have applied a cut score approach; however, there is evidence suggesting differences based on the classification approach -cut score versus latent profiles (Thayer et al, 2021). For instance, some authors suggested that the cut-score approach was more likely to identify the extreme groups (i.e., the Complete Mental Health and Troubled) while the latent profile analysis was more likely to identify the middle groups (i.e., the Symptomatic but Content and Vulnerable) (Thayer et al, 2021). This evidence requires further insights into the advantages and disadvantages of these different methodological approaches, through the implementation of studies that might simultaneously test different classification methods.…”
Section: Implications For Research and Practicementioning
confidence: 99%